2005
DOI: 10.1523/jneurosci.2467-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Wasting Disease of Elk: Transmissibility to Humans Examined by Transgenic Mouse Models

Abstract: Chronic wasting disease (CWD), a prion disease affecting free-ranging and captive cervids (deer and elk), is widespread in the United States and parts of Canada. The large cervid population, the popularity of venison consumption, and the apparent spread of the CWD epidemic are likely resulting in increased human exposure to CWD in the United States. Whether CWD is transmissible to humans, as has been shown for bovine spongiform encephalopathy (the prion disease of cattle), is unknown. We generated transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
252
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(275 citation statements)
references
References 23 publications
15
252
2
1
Order By: Relevance
“…Whereas the elk PrP expressing mice developed disease after only 118-142 days post-inoculation, human PrP expressing mice (129M) did not develop any features of TSE after more than 657 or more than 756 days [41]. In accordance with these results, Tamgüney et al also reported that human PrP overexpressing mice were not susceptible to nine CWD isolates from mule deer, white-tailed deer, and elk [84].…”
Section: Human Susceptibility To Cwdmentioning
confidence: 65%
See 3 more Smart Citations
“…Whereas the elk PrP expressing mice developed disease after only 118-142 days post-inoculation, human PrP expressing mice (129M) did not develop any features of TSE after more than 657 or more than 756 days [41]. In accordance with these results, Tamgüney et al also reported that human PrP overexpressing mice were not susceptible to nine CWD isolates from mule deer, white-tailed deer, and elk [84].…”
Section: Human Susceptibility To Cwdmentioning
confidence: 65%
“…At the National Prion Disease Pathology Surveillance Center at Case Western Reserve University (Cleveland, Ohio), Creutzfeldt-Jakob disease (CJD) suspect cases are studied and classified by CJD subtype. Thus far, twentyseven CJD patients who regularly consumed venison were reported to the Surveillance Center, however there have been no unusual or novel prion subtypes that might indicate the appearance of a new prion strain [7,41].…”
Section: Human Susceptibility To Cwdmentioning
confidence: 99%
See 2 more Smart Citations
“…En Amérique du Nord sont ainsi apparues l'encéphalopathie du vison et la maladie du dépérissement chronique des cervidés (chronic wasting disease : CWD) [16]. Cette dernière, qui se répand dans les groupes d'animaux sauvages, représente un sujet d'inquiétude important pour la santé animale bien que pour le moment aucun risque pour l'homme n'a pu être formellement identifié [17].…”
Section: Revuesunclassified